The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1103/physrevd.61.096002
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of the expansion of the renormalization group flow equation

Abstract: We compare and discuss the dependence of a polynomial truncation of the effective potential used to solve exact renormalization group flow equation for a model with fermionic interaction (linear sigma model) with a grid solution. The sensitivity of the results on the underlying cutoff function is discussed. We explore the validity of the expansion method for second and first-order phase transitions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 31 publications
6
84
0
Order By: Relevance
“…For details of the QCD aspects of this approach see the reviews [213] and [17] for a discussion of the phase diagram. Similar nonperturbative renormalization group studies of QCD motivated models can be found in [214,215,216]. Field theories with scalars and fermions have been investigated using similar techniques in [217,218,219,220].…”
Section: Introductionmentioning
confidence: 91%
“…For details of the QCD aspects of this approach see the reviews [213] and [17] for a discussion of the phase diagram. Similar nonperturbative renormalization group studies of QCD motivated models can be found in [214,215,216]. Field theories with scalars and fermions have been investigated using similar techniques in [217,218,219,220].…”
Section: Introductionmentioning
confidence: 91%
“…From the explicit solutions (20) and (22) we deduce that α = −1 for the sharp cut-off, and α = 0 for the optimal regulator. Deriving the correct value for α from the large-n behaviour of a n seems to be the most difficult part of the reconstruction problem.…”
Section: From Erg To Ptrgmentioning
confidence: 99%
“…This set of functions is particularly important since it is the standard set used for analytical considerations [12,13] or numerical applications [20,24,25,26] of the PTRG. For m ≥ d 2 , this function satisfies the basic requirements imposed on f k (Λ, s).…”
Section: From Ptrg To Ergmentioning
confidence: 99%
See 1 more Smart Citation
“…From our numerical calculation shown in the next section, the symmetry restoration and meson mass spectra at finite temperature are not sensitive to the choice of the cutoff function [32].…”
Section: Application Of Functional Renormalization To Thementioning
confidence: 99%